Business negotiations and the law : the protection of weak professional parties in standard form contracting - Rinaldo, Carlotta (New York : Routledge, 2020)
"Business Negotiations and the Law: The Protection of Weak Professional Parties in Standard Form Contracting aims to explore the issues surrounding contract negotiations between entrepreneurs and other professionals when one of the parties does not have the same level of bargaining power as the other. The need to protect weaker parties from unfair contract terms exists not only in relationships between businesses and consumers, but in business to business contracts also. This book focuses on the problem of small enterprises, independent contractors and other professional weak parties and examines these from a European point of view. There are significant differences between Member States as to decisions regarding regulatory context on the protection of weaker professional parties in asymmetrical contractual situations. However, European businesses are overwhelmingly smaller in size, so protecting weaker parties becomes key in facilitating successful and efficient negotiations. The book provides a critical and comparative overview of the area and recent regulatory developments, both to clarify the direction that European legislation is heading, and to explore the tools needed to assure the effectiveness of the common market. This text will be of interest to policy makers, researchers of European legislation, and students of commercial and business law"--
OCLC-licensed vendor bibliographic record.
Keywords: Commercial law -- Europe; Business enterprises -- Law and legislation -- Europe; Negotiation in business -- Europe; Contracts -- Europe; BUSINESS & ECONOMICS / Business Law; LAW / General; LAW / Business & Financial